Children With Developmental Coordination Disorder Show Altered Visuomotor Control During Stair Negotiation Associated With Heightened State Anxiety - Parr, Johnny V. V.; Foster, Richard J.; Wood, Greg; Thomas, Neil M.; Hollands, Mark A. (Frontiers in Human Neuroscience, 2020)
Safe stair negotiation is an everyday task that children with developmental coordination disorder (DCD) are commonly thought to struggle with. Yet, there is currently a paucity of research supporting these claims. We investigated the visuomotor control strategies underpinning stair negotiation in children with (N = 18, age = 10.50±2.04 years) and without (N = 16, age = 10.94±2.08 years) DCD by measuring kinematics, gaze behaviour and state-anxiety as they ascended and descended a staircase. A questionnaire was administered to determine parents’ confidence in their child’s ability to safely navigate stairs and their child’s fall history (within the last year). Kinematics were measured using three-dimensional motion capture (Vicon), whilst gaze was measured using mobile eye-tracking equipment (Pupil labs). The parents of DCD children reported significantly lower confidence in their child’s ability to maintain balance on the stairs and significantly more stair-related falls in the previous year compared to the parents of typically developing (TD) children. During both stair ascent and stair descent, the children with DCD took longer to ascend/descend the staircase and displayed greater handrail use, reflecting a more cautious stair negotiation strategy. No differences were observed between groups in their margin of stability, but the DCD children exhibited significantly greater variability in their foot-clearances over the step edge, which may increase the risk of a fall. For stair descent only, the DCD children reported significantly higher levels of state-anxiety than the TD children and looked significantly further along the staircase during the initial entry phase, suggesting an anxiety-related response that may bias gaze towards the planning of future stepping actions over the accurate execution of an ongoing step. Taken together, our findings provide the first quantifiable evidence that (a) safe stair negotiation is a significant challenge for children with DCD, and that (b) this challenge is reflected by marked differences in their visuomotor control strategies and state-anxiety levels. Whilst it is currently unclear whether these differences are contributing to the frequency of stair-related falls in children with DCD, our findings pave the way for future research to answer these important questions.